Kristal Hemoglobin Pada Bercak Darah yang Dipaparkan Sodium Hipoklorit (NaOCl) Menggunakan Tes Teichmann Dan Tes Takayama - Romdonah Romdonah; Radha Zatti Rahmi; Tegar Mohammad Indrayana; Fridayenti Fridayenti; Enikarmila Asni (Fakultas Kedokteran Universitas Riau, 2017)
Bloodstains is an important body fluids as evidence, because the blood has hemoglobin structure consisting of hemeand polypeptides. Perpetrators will attempt to clean the bloodstain that found at the crime scene by using cleaningagents and chemicals. Sodium hypochlorite is a chemical that found in cleaning fluids and bleach. This study aims toknow the effects of sodium hypochlorite to bloodstain and confirmatory test. Bloodstain on the objeck glasses andthe fabrics exposed by sodium hypochlorite concentration 5,25% and 0,15%, and examined with Teichmann’s testand Takayama’s test, and seen under microscope. In this study, show no crystal hemoglobin of the bloodstain on theobjeck glasses and fabrics exposed by sodium hypochlorite concentration 5.25% and concentration 0,15%. Thismight caused by sodium hypochlorite destructed structure of heme, so there were no reaction between heme, sodiumchloride and acetat glacial acids on Teichmann’s test and no reaction between heme and Takayama’s reagen onTakayama’s test. The conclusions of this study, crystal hemoglobin were not found on bloodstain exposed by sodiumhypochloryte using Teichmann’s test and Takayama’s test.